The Effectiveness of Artificial Intelligence Platforms in Creating Digital Educational Content - Christine Helena Natalia; Yuni Khairina; Immanuel Prasetya Gintings; Anni Holila Pulungan; Khairunnisa Br. Batubara (Sustainable, 2024)
This study investigates the effectiveness of Artificial Intelligence (AI) tools in enhancing digital content creation within project-based learning (PBL). Conducted at the Department of English Language and Literature, specifically the English Education Study Program, Faculty of Languages and Arts, Universitas Negeri Medan, the research focuses on students enrolled in the Digital Education Content Creator subject. The objective of the study is to evaluate the effectiveness of Artificial Intelligence (AI) in enhancing the quality of educational video content compared to conventional methods within a project-based learning framework. The research used a randomized sampling method, involving 80 students divided into two groups: an experimental group of 40 students using AI tools and a control group of 40 students relying on traditional approaches. Both groups created videos assessed based on six key criteria: content quality and relevance, clarity and structure, engagement, technical quality, duration and tempo, and accessibility and usability. The results show that the experimental group achieved significantly higher post-test scores, with an average of 3.8 compared to 2.64 in the control group. Hypothesis testing also supports these findings, with a t-test result exceeding the critical value. The findings confirm that AI tools significantly improve content quality, enabling students to produce more relevant, accessible, and technically refined digital content within a PBL framework. Future research should address AI's long-term effectiveness in different subject areas, accessibility challenges, and ethical concerns in education.